B cell depletion therapy in systemic lupus erythaematosus: relationships among serum B lymphocyte stimulator levels, autoantibody profile and clinical response. Issue 7 (25th October 2007) - Cambridge, G; Isenberg, D A; Edwards, J C W; Leandro, M J; Migone, T-S; Teodorescu, M; Stohl, W
Abstract : Objective: To assess the relationships between serum B lymphocyte stimulator (BLyS) levels, autoantibody profile and clinical response in patients with systemic lupus erythaematosus (SLE) following rituximab-based B cell depletion therapy (BCDT). Methods: A total of 25 patients with active refractory SLE were followed for ⩾1 year following BCDT. Disease activity was assessed using the British Isles Lupus Assessment Group (BILAG) system, and serum levels of BLyS and autoantibodies to dsDNA and extractable nuclear antigens (ENA) measured by ELISA. Serum immunoglobulins and anti-dsDNA antibodies were assessed for expression of the 9G4 idiotope (indicating VH4–34 germline gene origin). Results: Following BCDT, all patients depleted in the peripheral blood and improved clinically for ⩾3 months. Pre-BCDT BLyS levels were quantifiable (median 1.9 ng/ml) in 18/25 patients and rose in most patients at 3 months post-BCDT (median 4.15 ng/ml). Nine patients, all with quantifiable pre-BCDT serum BLyS, experienced a disease flare within 1 year. This group of patients was more likely to harbour anti-Ro/SSA antibodies (odds ratio 1.76; p = 0.06) with higher serum levels (p = 0.0027; Mann–Whitney U test). Serum levels of anti-ribonucleoprotein (RNP)/Sm were also higher in this group (p<0.05). Expression of VH4–34 by serum immunoglobulins and anti-dsDNA antibodies had no predictive value for the length of clinical response. Conclusions: Patients with SLE with an expanded autoantibody profile and raised BLyS levels at baseline had shorter clinical responses to BCDT. This may reflect a greater propensity to, and degree of, epitope spreading in such patients and suggests that treatment regimens beyond BCDT may be necessary to induce long-lasting clinical remissions in these individuals.